A tyranny against itself : intimate partner violence on the margins of Bogotá - Bhadra-Heintz, John I. B. (University of Pennsylvania Press, 2022)
Usme, one of the peripheral districts surrounding Bogotá, Colombia, is one of the poorest, most populous, and most marginalized outer districts of the city, with a high concentration of indigenous occupants. Over eighty percent of Usme's women have experienced partner violence or some kind of partner-controlling behavior. How does one go about understanding the perpetration of partner violence? Based on ethnographic work with survivors, responders, and most of all the perpetrators of this kind of abuse, scholar John I.B. Bhadra-Heintz explores this issue in A Tyranny Against Itself. Throughout this study, Bhadra-Heintz examines how this violence is made possible, how it is positioned to be permissible socially, and what is at stake for those who are involved. This violence is examined as a question of sovereignty on the intimate scale. Not the product of a particular cultural pathology, a phenomenon that can otherwise be otherized, this book seeks instead to find the lines of connection, and contradiction, that tie these intimate acts of violence into broader regimes of power. In a community so profoundly shaped by centuries of political conflict, only through this kind of approach can new apertures for engagement be found. Through them, this book outlines new vulnerabilities in this form of abuse, and along the way imagines new ways of escaping from these everyday acts of intimate terror and the broader systems of violence in which they are involved.